The Influence of Financial Performance and Profit Management on Company Value - Manurung, Lambok; Ningsi, Etty Harya (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study explores the critical factors influencing corporate value, focusing on financial performance and earnings management within the context of manufacturing sector companies listed on the Indonesia Stock Exchange from 2017 to 2021. Corporate value, indicative of company worth and investor confidence, is significantly influenced by financial performance, typically measured by metrics like return on assets (ROA). Higher ROA signals better profitability and enhances shareholder returns, thereby elevating corporate value. Conversely, earnings management practices, aimed at manipulating reported profits, do not significantly impact corporate value in this study, reflecting potential ethical concerns and the divergence of interests between managers and shareholders. These findings underscore the complex dynamics influencing corporate valuation and highlight the need for further research to elucidate these relationships amidst varying economic conditions.